Dynamic behaviors of a Leslie-Gower predator-prey model with Smith growth and constant-yield harvesting - Mengxin He; Zhong Li (Electronic Research Archive)
A Leslie-Gower predator-prey model with Smith growth and constant-yield harvesting is proposed in this paper. We show that the system admits at most two boundary equilibria, both of which are unstable. The degenerate positive equilibrium of the system is a cusp of codimension 2, and the system undergoes cusp-type Bogdanov-Takens bifurcation of codimension 2. Moreover, we prove that the system has a weak focus of order at most 3, and the system can undergo a degenerate Hopf bifurcation of codimension 3. Our results reveal that the constant-yield harvesting can lead to richer dynamic behaviors.